The effects of octreotide on gastric lesions and gastric mucosal barrier in rats which applied stress - Cihat GÜZEL; Zeki KANAY; Abdurrahman ÖNEN; Doğan KURT; Orhan DENLİ and Fikri CANORUÇ (Turkish Journal of Gastroenterology, 2019)
-